Design and implementation of trans-department graduation management system in digital campus - Su-mei WANG; Qian-yi WANG; Tian-ping LAI; Xiao-nan LI; Chun FAN; Yi-ming PENG; Guo-ping FAN (Tongxin xuebao)
Graduation management system is the typical case of trans-department applications in digital campus,having very high requirements of information integration,data exchange and real-time.An easily-extensible,adaptive system architecture and triple permission mechanism was designed and developed,not only to meet the school's graduation business processes,but also to provide a rich and efficient business management,security flexible access control and humanized service.